Pulmonary aspergilloma: from classification to management. (January 2020) - Harmouchi, Hicham; Sani, Rabiou; Issoufou, Ibrahim; Lakranbi, Marouane; Ouadnouni, Yassine; Smahi, Mohamed
Pulmonary aspergilloma is a form of aspergillosis characterized by the colonization of a preexisting pulmonary cavity, most often of tuberculosis origin. Clinical symptoms are predominately hemoptysis that can be life-threatening, and thoracic computed tomography can distinguish simple from complex pulmonary aspergilloma. The best therapeutic option remains surgery which allows surgical resection of the mycetoma and the underlying cavity. Nonsurgical treatment is performed in inoperable patients because of severe respiratory failure or a poor general condition.